Work-Related Factors and Individual Characteristics on Asthenopia Symptoms among “Pecanting Batik” Workers in Klaten, Indonesia - Risa Septi Astutik; Yuliani Setyaningsih; Daru Lestantyo (Jurnal Kesehatan Masyarakat, 2025)
Astenopia is associated with close work, such as blurred vision, diplopia, dry eyes, and headaches. The incidence of asthenopia is quite common among workers who perform intensive visual tasks. The goal is to analyze the risk factors that are most related to astenopia complaints. This type of observational research with a cross sectional study design was conducted in July 2024 on 155 batik canters in 45 batik-making home industries in Jarum Village, Klaten Regency, Central Java, Indonesia. Variables were measured using a general questionnaire containing questions on age, length of service, length of work, and length of rest. In addition, the Pittsburgh Sleep Quality Index (PSQI) questionnaire is used to measure sleep quality. The worker's awkward posture was measured using the Rapid Upper Limb Assessment Worksheet. And the distance to see the object is measured using the JOYKO brand 30cm Butterfly Iron Ruler between the object and the worker's eyes. The Visual Fatigue Index (VFI) questionnaire was used to measure astenopia complaints. The analysis of bivariate data with spearman rank and multivariate correlation was used multiple linear regression test. The results of this study showed that the majority of respondents were 44,368 years old on average, felt that their sleep quality was not good and had been working as a batik maker ≥ 10 years. And the risk factors most related to astenopia complaints are sleep quality (p=0.000), age (p=0.001), and working period (p=0.019).